Design of A Tool to Counter Objects with A Pear Sensor as A Fan and Light Controller Based on An Rtc Based on An ATmega 8535 Microcontroller - Faisal Ari Fitra (International Journal of Basic and Applied Science, 2022)
The need for a sense of comfort is one that is very important in human life. Likewise with comfort in a room, especially in the comfort of the office, especially in the boardroom, on campus. The purpose of the design and manufacture of the PIR sensor is as a controller and counter the man when it went into a room, the fan in the living room with a temperature above normal. Hopefully, by the automation system controls the fan and lights in the room temperature can be maintained to keep the temperature stable, and live according to the light intensity of the light that has been programmed.